Implementation of Material Requirement Planning (MRP) on The Procurement of Natural Materials of The KM 48+600 Karawang Toll Road Widening - Ariyanto, Sony (Universitas Mercu Buana, 2020)
Trading companies or manufacturing companies and service companies always have inventory. It is expected that MRP will be able to provide a solution to find out what methods can minimize inventory or storage costs. Procurement costs consist of the total cost of inventory with the cost of purchasing materials. In the procurement of natural materials, PT Kumala Wandira Danarta sets a maximum inventory cost of 5% of the procurement cost. This is to minimize costs resulting from inventory.Therefore, the application of MRP was chosen as a tool for controlling inventory costs through lot sizing methods including Lot For Lot, Period Order Quantity, Fixed Period Requirement, and Fixed Order Quantity. And the result is that all of these lot sizing techniques produce inventory costs below 5% of procurement costs and the Fixed Period Requirement becomes the lot sizing method with the lowest inventory cost, amounting to Rp. 11,490,000 and procurement costs Rp. 716,365,000.